Three noninvasive methods in the evaluation of subclinical cardiovascular disease in patients with acromegaly: epicardial fat thickness, aortic stiffness and serum cell adhesion molecules. (12th December 2013) - Topaloglu, Oya; Sayki Arslan, Muyesser; Turak, Osman; Ginis, Zeynep; Sahin, Mustafa; Cebeci, Muhammet; Ucan, Bekir; Cakir, Evrim; Karbek, Basak; Ozbek, Mustafa; Cakal, Erman; Delibasi, Tuncay
Summary Context Several studies have reported increased risk of cardiovascular disease due to early development of endothelial dysfunction and structural vascular changes in patients with acromegaly. Objective The aim of this study was to evaluate subclinical cardiovascular disease with epicardial fat thickness (EFT), aortic stiffness and serum levels of cell adhesion molecules (CAMs) in patients with acromegaly. Design Cross‐sectional study. Patients Twenty‐seven patients with active acromegaly (AA), 13 patients with remission acromegaly (RA) and 37 age‐ and sex‐matched healthy controls were studied. Measurements Epicardial fat thickness was evaluated by transthoracic echocardiography (TTE). Aortic stiffness (β) index, aortic strain (AoS) and aortic distensibility (AoD) were calculated from the aortic diameters measured by TTE. Serum levels of CAMs such as intercellular adhesion molecule (ICAM)‐1, vascular cell adhesion molecule (VCAM)‐1 and E‐selectin were measured. Results Epicardial fat thickness was significantly increased in patients with RA and AA as compared to controls 9·71 ± 1·54 and 10·08 ± 1·95 mm vs 5·74 ± 0·92 mm, P < 0·001, respectively). A significant positive correlation was found between the EFT and growth hormone (GH) levels (r = 0·365, P = 0·024). β‐index was similarly higher in patients with RA and AA than controls (15·68 ± 7·27 and 11·90 ± 8·24 vs 6·85 ± 2·87, P < 0·001, respectively). AoS and AoD were significantly decreased in patients with RA and AA as compared to the control group (3·81 ± 1·94 and 3·68 ± 1·99 vs 8·19 ± 4·19%, P < 0·001, respectively; and 1·21 ± 0·66 and 1·18 ± 0·63 vs 2·58 ± 1·50, 10−6 cm2/dyn, P < 0·001, respectively). Serum ICAM‐1 and VCAM‐1 levels were significantly higher in patients as compared to the control group (P < 0·001 vs P = 0·032, respectively). There were no significant differences in EFT, AoD, AoS, β‐index and serum CAMs between two patients groups (AA vs RA, P > 0·05). There was a significant negative correlation between E‐selectin and AoD (r = −0·45, P = 0·008). In multiple linear regression analysis, EFT was found to be associated with GH levels (β‐coefficient = 0·575, P = 0·008). Conclusion This study suggests that EFT and risk of subclinical cardiovascular disease are increased in patients with acromegaly. Serum GH level is an independent risk factor for EFT.